2023
DOI: 10.1002/adfm.202304985
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Topochemical Transformation of ZnIn2S4 for Efficient Photocatalytic Oxidation of 5‐Hydroxymethylfurfural to 2,5‐Diformylfuran

Abstract: Photocatalytic selective oxidation of 5‐hydroxymethylfurfural (HMF) coupled H2 production offers a promising approach to producing valuable chemicals. Herein, an efficient in situ topological transformation tactic is developed for producing porous O‐doped ZnIn2S4 nanosheets for HMF oxidation cooperative with H2 evolution. Aberration‐corrected high‐angle annular dark‐field scanning TEM images show that the hierarchical porous O‐ZIS‐120 possesses abundant atomic scale edge steps and lattice defects, which is ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 55 publications
1
3
0
Order By: Relevance
“…Active oxygen species might be assigned to the peak at 1170 cm −1 [26] . Moreover, the formation of (CH 2 OH)C 4 H 2 O(CO)* intermediate were observed at 1600 cm −1 rather than (CH 2 O)C 4 H 2 O(CHO)* at 1084 cm −1 as reported before [7b] . Therefore, it is suggested that TBUPP−Cu adsorbs HMF via the hydrogen bonds, and oxidise it upon light irradiation to generated HMFCA via the (CH 2 OH)C 4 H 2 O(CO)* intermediate.…”
Section: Resultssupporting
confidence: 80%
“…Active oxygen species might be assigned to the peak at 1170 cm −1 [26] . Moreover, the formation of (CH 2 OH)C 4 H 2 O(CO)* intermediate were observed at 1600 cm −1 rather than (CH 2 O)C 4 H 2 O(CHO)* at 1084 cm −1 as reported before [7b] . Therefore, it is suggested that TBUPP−Cu adsorbs HMF via the hydrogen bonds, and oxidise it upon light irradiation to generated HMFCA via the (CH 2 OH)C 4 H 2 O(CO)* intermediate.…”
Section: Resultssupporting
confidence: 80%
“…97 Such surface vacancies were beneficial for electron accumulation and substrate adsorption, thus the H 2 evolution rate was eight times higher than that of CdS-P. Zhu et al treated ZnIn 2 S 4 nanowires with oxygen plasma for 2 min and obtained a hierarchical porous O-ZIS-120 photocatalyst. 31 It showed the highest H 2 evolution rate of 1522 μmol h −1 g −1 in the current literature.…”
Section: Combination Of Photocatalytic Oxidation With H2 Evolution Or...mentioning
confidence: 80%
“…30 Moreover, owing to the unique redox ability of photogenerated electrons (e − ) and holes (h + ) in the photocatalytic system, selective oxidation and reduction can simultaneously occur over the same catalyst. In such a context, H 2 evolution 31,32 or CO 2 reduction 33 can be simultaneously performed with photoconversion of FAL and HMF. Besides, the tandem photoreduction and oxidation of FAL can yield tetrahydrofurfuryl alcohol (THFA) and γ-butyrolactone (GBL).…”
Section: Introductionmentioning
confidence: 99%
“…Artificial photosynthesis represents the most viable and promising strategy for achieving carbon neutrality . Among its various forms, photocatalyst-based hydrogen (H 2 ) evolution from overall water splitting has garnered significant research attention, which offers a potential option to replacing conventional fossil fuels with clean and renewable energy sources. However, the H 2 evolution performance is constrained by unfavorable thermodynamics, sluggish kinetics, and rapid inverse reactions. , The solution of incorporating hole sacrificial agents also results in wasting the oxidation ability of photogenerated holes and exacerbating product separation challenges due to the emergence of undesirable byproducts. Impressively, photocatalytic H 2 evolution coupled with value-added chemicals synthesis via the effective utilization of photogenerated electrons and holes is a win-win strategy for sustainable development. …”
Section: Introductionmentioning
confidence: 99%